2014
DOI: 10.1175/jpo-d-13-0242.1
|View full text |Cite
|
Sign up to set email alerts
|

The Red Sea: A Natural Laboratory for Wind and Wave Modeling

Abstract: The Red Sea is a narrow, elongated basin that is more than 2000 km long. This deceivingly simple structure offers very interesting challenges for wind and wave modeling, not easily, if ever, found elsewhere. Using standard meteorological products and local wind and wave models, this study explores how well the general and unusual wind and wave patterns of the Red Sea could be reproduced. The authors obtain the best results using two rather opposite approaches: the high-resolution Weather Research Forecasting (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 31 publications
0
63
0
Order By: Relevance
“…Monsoon winds have been shown to be critical drivers of phytoplankton seasonal variability in other subtropical areas such as Sanya Bay (South China Sea), where the occurrence of summer and winter blooms correspond to monsoon winds [36]. Wind fields from a high resolution, downscaled assimilated product [37,38] were used to analyse the atmospheric variability, since it provides higher resolutions compared to publicly available wind datasets and assimilates all available in situ data in the region. The atmospheric product was developed at KAUST by the Earth Modeling and prediction group, using the Advanced Research–Weather Research and Forecasting atmospheric model [39].…”
Section: Methodsmentioning
confidence: 99%
“…Monsoon winds have been shown to be critical drivers of phytoplankton seasonal variability in other subtropical areas such as Sanya Bay (South China Sea), where the occurrence of summer and winter blooms correspond to monsoon winds [36]. Wind fields from a high resolution, downscaled assimilated product [37,38] were used to analyse the atmospheric variability, since it provides higher resolutions compared to publicly available wind datasets and assimilates all available in situ data in the region. The atmospheric product was developed at KAUST by the Earth Modeling and prediction group, using the Advanced Research–Weather Research and Forecasting atmospheric model [39].…”
Section: Methodsmentioning
confidence: 99%
“…The MODIS-Terra true color image from 23 June shows a pronounced dust plume emanating from the vicinity of Tokar and extending out over the Red Sea. This is facilitated by strong winds blowing from west to east caused by large land/ocean temperature gradients that occur in this area predominantly in July [63][64][65]. The ASCAT surface wind stress field from 24 June indicates that the winds that produced the dust uplift were likely also affecting the sea surface during this time.…”
Section: Temporal and Spatial Variations Of Chl-a Concentration-relatmentioning
confidence: 96%
“…However, it is likely that the 0.33 • resolution of the OSCAR data is insufficient to resolve the pair of cyclonic eddies apparent in the higher resolution SSH data. The formation of an eddy dipole in the western Red Sea near 19 • N with a cyclonic eddy to the north and an anticyclonic eddy to the south has been attributed to the influence of a wind jet associated with the Tokar Gap [59], which is active throughout the boreal summer [3,[63][64][65] and a large source of atmospheric dust [66]. is associated with locally cooler SSTs, even though the SSH is elevated.…”
Section: Temporal and Spatial Variations Of Chl-a Concentration-relatmentioning
confidence: 99%
“…In a recent paper, Langodan et al [2014] reported positive results from the simulation of the wave conditions in the Red Sea, provided that the input ECMWF wind speeds were slightly increased. This is consistent with multiple previous results (see, among others, Cavaleri and Bertotti [2004]), indicating that, like other global model results, the ECMWF surface wind speeds are of good quality over the oceans, but have a marked tendency to underestimate the wind blowing from the coast, a fact relevant particularly in the inner seas.…”
Section: A Discussion Of the Resultsmentioning
confidence: 99%